2020
DOI: 10.18502/jfrh.v14i1.3784
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of Infertile Women Candidates for Egg Donation: A Qualitative Study

Abstract: Objective: Women with premature ovarian insufficiency, menopause, gonadal dysgenesis, and genetic disorders as well as those with a history of recurrent in vitro fertilization failure may benefit from the assisted fertility techniques. These women experience concerns that directly affect their married life especially in egg donation treatment. This study was conducted to investigate the reproductive health concerns of infertile women who were candidates for egg donation. Materials and methods: This quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
1
6
1
2
Order By: Relevance
“…Consistent with our study, in a study, the greatest source of women's emotional support was their husbands [ 24 , 46 ] while Orshan founded one of the most common experiences of the women was a perceived lack of support from their health care providers regarding the symptoms that eventually led to a diagnosis of POI [ 29 ]. Unlike our findings, in a latest study, women complained for lack of supportive situation, which included lack of family support, lack of socio-economic support, and scattered information support [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Consistent with our study, in a study, the greatest source of women's emotional support was their husbands [ 24 , 46 ] while Orshan founded one of the most common experiences of the women was a perceived lack of support from their health care providers regarding the symptoms that eventually led to a diagnosis of POI [ 29 ]. Unlike our findings, in a latest study, women complained for lack of supportive situation, which included lack of family support, lack of socio-economic support, and scattered information support [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that, one of the most common concerns of participants was changing in menstrual bleeding pattern and infertility that resulted to endangerment of women's health. While, This findings is similar to other researches [ 24 , 38 ], founded afflicted women are concern about infertility and amenorrhea, in Bagheri et al study sexual relationship was the most important concern of almost all participants [ 39 ]. Contrary to our study, Groff et al [ 24 ] concluded that women generally had a good idea of their health.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations